A Qualitative Content Analysis of Copywriting Elements in @batiksalmacirebon Instagram Posts (March–October 2025) - Eko Agung Sugiyarto; Marlinda Irwanti Poernomo; Maryami (Communica : Journal of Communication, 2026)
The rapid growth of digital media has encouraged businesses to increasingly utilize Instagram as a marketing communication platform. This study aims to identify the copywriting elements and categories of advertising copy used in Instagram posts on the @batiksalmacirebon account. Employing a qualitative descriptive approach and content analysis method, the study analyzed a dataset of 187 Instagram posts published between March 1 and October 25, 2025. Data were collected through non-participant observation and documentation of posts containing copywriting elements. The findings reveal that the account consistently applies key copywriting components, particularly headlines, subheadlines, and body copy, while taglines and slogans were not identified in the analyzed posts. Furthermore, the analysis classified the advertising messages into ten copywriting categories, with factual, “you and me,” and teaser copy emerging as the most frequently used forms. The study contributes to social media marketing literature by providing a systematic mapping of copywriting structures and categories employed in Instagram-based batik promotion, offering a clearer understanding of how local creative industry brands communicate through digital platforms. The findings also provide insights into the strategic use of copywriting to support branding and promotional communication for cultural products. However, this study is limited to mapping copywriting structures and categories and does not evaluate audience responses, engagement levels, or the persuasive effectiveness of the advertising messages.